KEPASTIAN HUKUM AKTA PERJANJIAN HUTANG PIUTANG DAN JAMINAN YANG DIJADIKAN DASAR JUAL BELI TANAH. - Amanda, Janice; Hutomo, Putra; Basuki, Basuki (LPPM Institut Pendidikan Nusantara Global, 2024)
Legal certainty in the context of the deed of agreement on debts and guarantees that are the basis for the purchase and sale of land. so that the parties involved in the transaction can obtain legal clarity and security regarding debt-receivable obligations and rights and responsibilities related to guarantees, creating a solid foundation for the implementation of land sale and purchase transactions. This study raises two problems, namely the legal consequences of the cancellation of the debt and accounts receivable agreement accompanied by a guarantee in the sale and purchase of land and legal certainty deed of debt and Accounts Receivable Agreement and guarantee as the basis for sale and purchase by using the theory of legal consequences and The Theory of legal certainty. The method used in this study with the type of normative research is legal research with secondary data using primary, secondary and tertiary sources of legal materials. The research approach used is the approach of legislation, conceptual, case, and analytical and legal material collection techniques carried out by identifying and inventorying positive legal rules, researching library materials and other sources of legal materials relevant to the legal issues under study. Legal material analysis technique is done by legal interpretation (interpretation) grammatical, historical and systematic The results of this study that the legal certainty in the deed of agreement payable receivable for the sale and purchase of land form a solid foundation for the parties involved. Clarity regarding debt-receivable obligations and collateral-related responsibilities creates a stable legal environment, not only minimizing the potential for conflict, but also allowing transactionists to operate with confidence within a reliable legal framework. The role of the guarantee in the deed is the foundation that provides protection and trust in the land sale and purchase transaction, creating security for the creditor and confidence for the loan recipient. With clear guarantees, transaction actors can face the process of buying and selling land with more confidence, reducing financial risks that may arise.